Preparation method of biotite-based multi-active-center catalytic oxidation material

By constructing uniformly distributed iron-copper bimetallic sites on black mica, the problems of high cost and low stability of traditional catalytic oxidants in wastewater treatment are solved, and efficient and stable catalytic performance and low-cost wastewater treatment effects are achieved.

CN119215894APending Publication Date: 2024-12-31NANCHANG HANGKONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411352530.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Traditional catalytic oxidants have problems of high cost, low stability and unsatisfactory catalytic performance in wastewater treatment, especially when they are prone to inactivation under high temperature and mechanical impact conditions, and the preparation of bimetallic catalysts is complex and costly.

Method used

A multi-active center catalytic oxidation material preparation method based on black mica is used to construct uniformly distributed iron-copper bimetallic sites through gradient temperature control reaction, reduction treatment and ion exchange on black mica to form an efficient catalyst.

Benefits of technology

It achieves efficient and stable catalytic performance, reduces preparation cost and energy consumption, improves the mechanical strength and stability of the material, is suitable for different reaction conditions, and has good chemical stability and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215894A_ABST
    Figure CN119215894A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of novel catalytic materials, and discloses a biotite-based multi-active-center catalytic oxidation material preparation method, which comprises: 1, dispersing biotite in a hydrochloric acid solution, and carrying out mixing stirring to obtain acid-pretreated biotite; step 2, cleaning biotite pretreated with acid, mixing the biotite pretreated with a copper salt solution, and carrying out gradient temperature control reaction to obtain a mixture I; 3, dispersing the mixture I in deionized water, adjusting the pH value, mixing with a reducing agent for reduction reaction, and cleaning with deionized water to obtain a mixture II; and 4, dispersing the mixture II in a ferric salt solution, stirring, cleaning with deionized water, and freeze-drying to obtain the biotite-based multi-active-center oxidation catalytic material. According to the invention, accurate construction of copper and iron double-metal sites can be realized, the mechanical strength and stability of the catalyst can be improved, and the preparation cost and energy consumption are reduced, so that wide application of an advanced oxidation technology in wastewater treatment is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of novel catalytic materials, and in particular to a method for preparing a multi-active center catalytic oxidation material based on biotite. Background Art

[0002] With the continuous advancement of industrialization, the types and concentrations of organic pollutants in wastewater are increasing, posing a severe challenge to environmental protection. Advanced oxidation technology (AOPs) has become an important research direction in the field of wastewater treatment because of its ability to efficiently degrade refractory organic pollutants. Advanced oxidation technology can produce highly active hydroxyl radicals (·OH), rapidly oxidize and decompose organic pollutants, and is widely used in wastewater treatment. However, traditional advanced catalytic oxidants have many problems in practical applications, which limits their widespread application.

[0003] Traditional single metal catalysts have some significant disadvantages in advanced oxidation reactions. For example, common iron-based catalysts need to be calcined at high temperatures in their applications, which not only requires high-end equipment and increases capital investment, but also leads to high power consumption and high energy consumption, significantly increasing the preparation cost. Studies have shown that Fe 2 O 3 The specific surface area of ​​the nanoparticles significantly decreased after calcination at 350°C for 6 hours, resulting in reduced catalytic performance (Li et al., 2018). In addition, these catalysts have low mechanical strength and are easily damaged or detached due to mechanical impact or hydraulic erosion, affecting the service life and stability of the materials. For example, iron oxide particles formed by iron salts under high temperature conditions are easily broken under the impact of water flow, thereby losing activity (Zhang et al., 2019). In addition, the active components of the monometallic catalysts prepared by bonding are easily lost during use, resulting in catalyst failure and unstable catalytic effect. These shortcomings significantly limit the application of traditional monometallic catalysts in actual wastewater treatment.

[0004] In recent years, the catalytic efficiency of catalysts can be significantly improved by introducing bimetallic sites, especially copper and iron bimetallic sites, into catalytic materials. For example, the synergistic effect of copper and iron can effectively promote the activation of persulfate, thereby generating more highly active free radicals. Studies have found that Cu-Fe bimetallic catalysts can maintain efficient catalytic performance in the range of pH 3 to 9, which is wider than the applicable pH range of single iron-based catalysts (Wang et al., 2020). The mutual promotion of copper and iron not only accelerates the electron transfer rate, but also expands the pH application range of the catalyst, enabling it to maintain efficient catalytic performance under both acidic and alkaline conditions. However, the preparation of bimetallic catalysts also faces some challenges. For example, the construction of copper-iron bimetallic sites usually involves complex processes and needs to be carried out under high temperature and high pressure conditions. This not only increases the difficulty and cost of preparation, but also limits its large-scale application (Chen et al., 2021).

[0005] From nanoparticles to nanoclusters and then to the reduction of diatomic particle size, the catalytic performance of the catalyst has been gradually improved. Nanoparticles have a large specific surface area and high catalytic activity, but they are easy to agglomerate during the reaction, resulting in reduced catalytic efficiency. For example, studies have shown that Fe 3 O 4 Nanoparticles tend to agglomerate at high temperatures, resulting in a surface area of ​​150 m 2 / g reduced to 75m 2 / g, the catalytic efficiency is reduced by 40% (Yang et al., 2017). Nanoclusters exhibit higher catalytic activity and stability due to their smaller particle size and more surface active sites. For example, Au nanoclusters are 2 times more efficient than nanoparticles in photocatalytic degradation of organic pollutants (Huang et al., 2018). However, as the particle size is further reduced to the diatomic level, the activity and selectivity of the catalyst can be further improved, but the difficulty of preparation is also significantly increased. This is because diatomic catalysts require precise atomic arrangement and high structural control, which is difficult to meet with traditional preparation methods. For example, studies have shown that diatomic Cu catalysts have a high selectivity in CO 2 The catalytic activity in the reduction reaction is 30% higher than that of single atoms and nanoparticles, but its preparation needs to be carried out under ultra-high vacuum conditions, which is complex and costly (Liu et al., 2020). Therefore, it is urgent to develop a low-cost, long-lasting and stable catalytic oxidation material. Summary of the invention

[0006] The present invention is intended to provide a method for preparing a multi-active center catalytic oxidation material based on biotite, so as to solve the problem of unsatisfactory catalytic performance and high cost of the catalytic oxidation material in the prior art.

[0007] To achieve the above object, the present invention adopts the following technical solution: a method for preparing a multi-active center catalytic oxidation material based on biotite, characterized in that it comprises the following steps:

[0008] Step 1, dispersing biotite in a hydrochloric acid solution, mixing and stirring to obtain acid-pretreated biotite;

[0009] Step 2, washing the acid pretreated biotite and mixing it with the copper salt solution, and then reacting it under gradient temperature control to obtain a mixture I;

[0010] Step 3, dispersing the mixture I in deionized water, adjusting the pH value, mixing it with a reducing agent for reduction reaction, and washing with deionized water to obtain a mixture II;

[0011] Step 4: Disperse the mixture II in an iron salt solution, stir, wash with deionized water, and freeze-dry to obtain a biotite-based multi-active center oxidation catalytic material.

[0012] Preferably, as an improvement, in step 1, the particle size of biotite is less than 200 mesh, the concentration of hydrochloric acid is 0.1-1 mol / L, and the mixing and stirring time is 15-60 min.

[0013] Preferably, as an improvement, in step 2, the copper salt is CuCl 2 、Cu(NO 3 ) 2 At least one of the above, the concentration of copper salt is 0.1-1 mol / L, and the addition ratio of copper salt to biotite is 5g:(0.1-1 mol / L).

[0014] Preferably, as an improvement, in step 2, the gradient temperature control reaction is: heating and stirring at 30°C for 1h, then heating to 40°C at a rate of 10°C / h, heating and stirring for 2h, then heating to 50°C at a rate of 10°C / h, heating and stirring for 3h, then heating to 60°C at a rate of 10°C / h, heating and stirring for 4h, then heating to 70°C at a rate of 10°C / h, heating and stirring for 5h, then heating to 80°C at a rate of 10°C / h, and heating and stirring for 6h.

[0015] Preferably, as an improvement, in step three, the pH is adjusted to 1.2-1.5.

[0016] Preferably, as an improvement, in step three, the mixture I is dispersed in deionized water under anaerobic conditions at room temperature.

[0017] Preferably, as an improvement, in step 3, the reducing agent is NaBH 4 or KBH 4 , the molar ratio of the reducing agent to the copper in the mixture I is 10 to 30:1, and the reduction reaction time is 1 to 5 minutes.

[0018] Preferably, as an improvement, in step 4, the iron salt is FeCl 3 、Fe(NO 3 ) 3 At least one of the above, the concentration of the iron salt is 0.1-1 mol / L, and the addition ratio of the iron salt to the mixture II is (0.1-1 mol / L): 5 g.

[0019] Preferably, as an improvement, in step 4, the freeze-drying temperature is less than 40° C. and the freeze-drying pressure is less than 10 Pa.

[0020] Preferably, as an improvement, a multi-active center catalytic oxidation material based on biotite is prepared using any preparation method of claims 1 to 9, and the content of active iron in the material is 3wt% to 4wt%, and the content of active copper is 3.5 to 4.6wt%.

[0021] The principles and advantages of this solution are: in actual application, in this technical solution, in order to solve the problems of uneven distribution of copper and iron, easy deactivation of materials in the air and low activation efficiency in the prior art, this technical solution uses biotite as a template to prepare catalytic materials. Biotite is a common layered silicate mineral with a layered structure and a large specific surface area, which is conducive to adsorption and catalytic reactions. The layers carry negative charges and have good ion exchange capacity. It shows good chemical stability in both acidic and alkaline environments and is not easy to decompose or dissolve. Its thermal stability makes it suitable for high-temperature environments and helps to maintain its structure and function in high-temperature catalytic reactions. It is non-toxic, harmless, environmentally friendly, has abundant reserves, low mining costs, and good economy. The formed advanced catalytic oxidant material has strong mechanical strength, and the active components are evenly distributed in the molded particles. The catalyst will not be deactivated due to mechanical damage, hydraulic erosion, and other problems, and it has more stable and long-lasting catalytic performance. In addition, biotite can provide uniform nanopores and highly dispersed active sites. By using biotite as a template, not only can the precise construction of copper and iron bimetallic sites be achieved, but the mechanical strength and stability of the catalyst can also be improved, and the preparation cost and energy consumption can be reduced.

[0022] In terms of preparation technology, this technical solution uses batch temperature control to regulate the ion exchange and reduction process of active copper, iron and biotite, to achieve the optimal load and distribution of transition metal elements in two-dimensional space, thereby constructing active sites of iron-copper bimetallic reaction centers in a nano-confined environment. The physical / chemical stability of the material is intervened by a temperature-limited and time-limited process, so that the biotite interlayers are opened, the interlayer sites are replaced by Cu2+, and the copper ions are ensured to diffuse evenly between the biotite layers. The copper ions are continued to be adsorbed and fixed at a higher temperature to ensure the formation of a stable copper ion adsorption and fixed layer. Through ion exchange and adsorption, the iron ions are evenly distributed between the biotite layers to form a multi-active center structure, thereby significantly improving the stability and activity of the material and the stability and applicability under different reaction conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 (a) is a TEM image of the original biotite; (b) is a TEM image of the biotite-based multi-active center oxidation catalytic material involved in this application.

[0024] Figure 2 (a) is the catalytic removal kinetic curve of organic pollutants by different biotite-based multi-active site catalytic oxidation materials synthesized in Examples 1 to 5 of the present application; (b) is the catalytic removal rate of organic pollutants by different biotite-based multi-active site catalytic oxidation materials synthesized in Examples 1 to 5 of the present application.

[0025] Figure 3 (a) is the catalytic degradation efficiency of the bimetallic multi-active site catalytic oxidation material loaded with biotite in the embodiment of the present application and the catalytic degradation efficiency of the bimetallic material without biotite loading, representing the improvement of the bimetallic multi-active site catalytic oxidation material loaded with biotite relative to the bimetallic multi-active site catalytic oxidation material without biotite loading; (b) is the catalytic degradation efficiency of the bimetallic multi-active site catalytic oxidation material loaded with biotite and the bimetallic material without biotite loading for the catalytic removal rate of organic pollutants in the embodiment of the present application.

[0026] Figure 4 (a) is the catalytic removal kinetic curve of the multi-active site catalytic oxidation material based on biotite synthesized under different heating conditions in the examples of the present application; (b) is the catalytic removal rate of the multi-active site catalytic oxidation material based on biotite synthesized under different heating conditions in the examples of the present application.

[0027] Figure 5 (a) is the catalytic removal kinetic curve of different types of organic pollutants in the examples of the present application; (b) is the catalytic removal rate of different types of organic pollutants in the examples of the present application.

[0028] Figure 6This application is based on the statistical graph of catalytic removal rate of five repeated cycles of biotite multi-active center oxidation catalytic material. DETAILED DESCRIPTION

[0029] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.

[0030] Program Overview:

[0031] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0032] Step 1: Weigh 5 g of biotite powder with a size of less than 200 mesh, disperse 5 g of the biotite powder in a 0.1-1 mol / L hydrochloric acid solution, and mix and stir for 15-60 min to obtain acid-treated biotite.

[0033] Step 2: Wash with deionized water for 3 times, mix 5g of the washed acid-treated biotite with 0.1-1mol / L copper salt (such as CuCl 2 or Cu(NO 3 ) 2 ) solutions were mixed, heated at 30°C with stirring for 1 h, then heated to 40°C at a rate of 10°C / h, heated with stirring for 2 h, then heated to 50°C at a rate of 10°C / h, heated with stirring for 3 h, then heated to 60°C at a rate of 10°C / h, heated with stirring for 4 h, then heated to 70°C at a rate of 10°C / h, heated with stirring for 5 h, then heated to 80°C at a rate of 10°C / h, heated with stirring for 6 h to obtain a mixture I.

[0034] Step 3: Disperse the mixture I in oxygen-free deionized water in an anaerobic environment (such as a nitrogen environment) at room temperature, adjust the pH value to 1.2-1.5 with a hydrochloric acid solution, and then mix it with a reducing agent (such as NaBH 4 or KBH 4 ) are mixed for reduction reaction for 1 to 5 minutes, and then washed three times with oxygen-free deionized water to obtain a mixture II, wherein the molar ratio of the reducing agent to the copper in the mixture I is 10 to 30:1.

[0035] Step 4: Disperse 5 g of mixture II in 0.1-1 mol / L iron salt (such as FeCl 3 or Fe(NO 3 ) 3) solution, stirred at room temperature for 4 to 8 hours, then washed three times with oxygen-free deionized water, and freeze-dried below -40°C and below 10Pa to obtain a multi-active center oxidation catalytic material based on biotite.

[0036] In the biotite-based multi-active center catalytic oxidation material, the content of active iron is 3wt% to 4wt%; the content of active copper is 3.5wt% to 4.6wt%.

[0037] Example 1

[0038] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0039] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.1mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it three times with oxygen-free deionized water in an oxygen-free glove box; then add 200ml 1mol / L CuCl 2 The solution was heated and stirred for 1 h in a 30 °C water bath and under a magnetic stirring of 400 rpm / min, and the temperature was increased at a rate of 7.5 °C / h, and the mixture was heated and mixed for 2 h every time the temperature was increased by 10 °C, and the mixture was heated to 60 °C and mixed for 3 h to obtain a mixture I; the mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 30:1 4 The suspension was quickly added, sealed quickly, reacted at room temperature for 1 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 0.5 mol / L FeCl 3 The solution was magnetically stirred at 400 rpm / min for 8 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, and the element concentration was measured with a flame spectrophotometer after digestion by wet digestion method, and the results showed that the content of active iron was 3.5wt% and the content of active copper was 4.1wt%.

[0040] Example 2

[0041] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0042] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.5mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 60min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it with oxygen-free deionized water in an oxygen-free glove box for 3 times; then add 200ml 0.1mol / L CuCl 2 The solution was heated and stirred for 1.5 h in a 30 °C water bath and 400 rpm / min magnetic stirring, and the temperature was increased at a rate of 10 °C / h, and the mixture was heated and mixed for 1 h every time the temperature was increased by 10 °C, and the mixture was heated to 70 °C and mixed for 4 h to obtain a mixture I; the mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 10:1 4 The suspension was quickly added, sealed quickly, reacted at room temperature for 3 minutes, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 1 mol / L FeCl 3 The solution was magnetically stirred at 400 rpm / min for 4 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, with an active iron content of 3.7wt% and an active copper content of 4.0wt%.

[0043] Example 3

[0044] A preparation method of a multi-active center catalytic oxidation material based on biotite, comprising the following steps: grinding biotite to 200 meshes, weighing 5g of biotite powder and adding it into a 250ml conical flask, then adding 200ml of 1mol / L hydrochloric acid solution, mixing under 400rpm / min magnetic stirring for 15min, then removing the supernatant by high-speed centrifugation at 8000rpm, washing 3 times with oxygen-free deionized water in an oxygen-free glove box; then adding 200ml of 0.5mol / L CuCl 2 The solution was heated and stirred for 2 h in a 30 °C water bath and 400 rpm / min magnetic stirring, and the temperature was increased at a rate of 5 °C / h, and the mixture was heated and mixed for 1.5 h every time the temperature was increased by 10 °C, and the mixture was heated to 80 °C and mixed for 2 h to obtain a mixture I; the mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 20:1 4The suspension was quickly added, sealed quickly, reacted at room temperature for 5 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 0.1 mol / L FeCl 3 The solution was magnetically stirred at 400 rpm / min for 6 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, with an active iron content of 3.6wt% and an active copper content of 4.2wt%.

[0045] Example 4

[0046] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0047] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.5mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it with oxygen-free deionized water in an oxygen-free glove box for 3 times; then add 200ml 0.5mol / L CuCl 2 The solution was heated and stirred for 2 h in a 30 °C water bath and 400 rpm / min magnetic stirring, and the temperature was increased at a rate of 10 °C / h, and the mixture was heated and mixed for 2 h every time the temperature was increased by 10 °C, and the mixture was heated to 80 °C and mixed for 4 h to obtain a mixture I; the mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 30:1 4 The suspension was quickly added, sealed quickly, reacted at room temperature for 3 minutes, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 0.5 mol / L FeCl 3 The solution was magnetically stirred at 400 rpm / min for 8 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, with an active iron content of 3.4wt% and an active copper content of 4.2wt%.

[0048] Example 5

[0049] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0050] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.1mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it three times with oxygen-free deionized water in an oxygen-free glove box; then add 200ml 1mol / L CuCl 2 The solution was heated and stirred for 1 h in a 30 °C water bath and under a magnetic stirring of 400 rpm / min, and the temperature was increased at a rate of 7.5 °C / h, and the mixture was heated and mixed for 2 h every time the temperature was increased by 10 °C, and the mixture was heated to 60 °C and mixed for 3 h to obtain a mixture I; the mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 30:1 4 The suspension was quickly added, sealed quickly, reacted at room temperature for 1 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 0.5 mol / L FeCl 3 The solution was magnetically stirred at 400 rpm / min for 8 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, with an active iron content of 3.5wt% and an active copper content of 4.1wt%.

[0051] Example 6

[0052] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0053] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.1mol / L hydrochloric acid solution, mix under 400rpm / min magnetic stirring for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, wash it with oxygen-free deionized water in an oxygen-free glove box for 3 times; add 200ml 0.5mol / L FeCl 3The solution was magnetically stirred at 400 rpm / min for 8 hours at room temperature, and then washed three times with oxygen-free deionized water; a biotite-based oxidation catalytic material suspension was obtained, and the suspension was freeze-dried for 24 hours to obtain a biotite-based catalytic oxidation material, with an active iron content of 3.9wt% and an active copper content of 0wt%.

[0054] Example 7

[0055] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0056] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.1mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it three times with oxygen-free deionized water in an oxygen-free glove box; then add 200ml 1mol / L CuCl 2 The solution was heated and stirred for 1 h in a 30 °C water bath and under a magnetic stirring of 400 rpm / min, and the temperature was increased at a rate of 7.5 °C / h, and the mixture was heated and mixed for 2 h every time the temperature was increased by 10 °C, and the mixture was heated to 60 °C and mixed for 3 h to obtain a mixture I; the mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 30:1 4 The mixture was quickly added to the suspension, sealed quickly, reacted at room temperature for 1 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain a biotite-based catalytic oxidation material suspension. The suspension was freeze-dried for 24 h to obtain a biotite-based catalytic oxidation material with an active iron content of 0 wt% and an active copper content of 4.5 wt%.

[0057] Example 8

[0058] Group 1: Nano copper powder;

[0059] Group 2: Iron salts (FeCl 3 );

[0060] Group 3: Nano copper powder + iron salt.

[0061] Example 9

[0062] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0063] The biotite was ground to 200 mesh, 5 g of biotite powder was weighed and added to a 250 ml conical flask, and then 200 ml of 0.1 mol / L hydrochloric acid solution was added, and mixed under 400 rpm / min magnetic stirring for 30 min, and then the supernatant was removed by high-speed centrifugation at 8000 rpm, and washed three times with oxygen-free deionized water in an oxygen-free glove box; then 200 ml of 1 mol / L CuCl2 solution was added, and heated and stirred for 20 h under 40°C water bath conditions and 400 rpm / min magnetic stirring, and then washed three times with deionized water to obtain a mixture I. The mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH4 was quickly added to the suspension according to a molar ratio of NaBH4 to Cu2+ of 30:1, and the suspension was quickly sealed and reacted at room temperature for 1 min. The supernatant was removed by high-speed centrifugation at 8000 rpm, and the mixture was washed 3 times with oxygen-free deionized water in an oxygen-free glove box to obtain a zero-valent copper biotite material. The zero-valent copper biotite material was added to 200 ml of 0.5 mol / L FeCl3 solution, and magnetically stirred at 400 rpm / min for 8 h at room temperature, and then washed 3 times with oxygen-free deionized water; a suspension of a multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 h to obtain a multi-active center catalytic oxidation material based on biotite, wherein the content of active iron was 1.4 wt%, and the content of active copper was 2.3 wt%.

[0064] Example 10

[0065] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0066] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.1mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it three times with oxygen-free deionized water in an oxygen-free glove box; then add 200ml 1mol / L CuCl 2 The solution was heated and stirred in a water bath at 60°C and magnetically stirred at 400 rpm / min for 20 h, and then washed three times with deionized water to obtain a mixture I. The mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 30:1 4The suspension was quickly added, sealed quickly, reacted at room temperature for 1 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 0.5 mol / L FeCl 3 The solution was magnetically stirred at 400 rpm / min for 8 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, with an active iron content of 1.7wt% and an active copper content of 2.8wt%.

[0067] Embodiment 11

[0068] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0069] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.1mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it three times with oxygen-free deionized water in an oxygen-free glove box; then add 200ml 1mol / L CuCl 2 The solution was heated and stirred in a water bath at 80°C and magnetically stirred at 400 rpm / min for 20 h, and then washed three times with deionized water to obtain a mixture I. The mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 30:1 4 The suspension was quickly added, sealed quickly, reacted at room temperature for 1 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 0.5 mol / L FeCl 3 The solution was magnetically stirred at 400 rpm / min for 8 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, with an active iron content of 4.1wt% and an active copper content of 4.0wt%.

[0070] Example 12

[0071] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0072] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.1mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it three times with oxygen-free deionized water in an oxygen-free glove box; then add 200ml 1mol / L CuCl 2 The solution was heated and stirred at 30°C with a magnetic stirrer at 400 rpm / min, and heated to 80°C at a heating rate of 2.5°C / h for 20 hours, and then washed three times with deionized water to obtain a mixture I. The mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 30:1 4 The suspension was quickly added, sealed quickly, reacted at room temperature for 1 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added to 200 ml 0.5 mol / LFeCl 3 The solution was magnetically stirred at 400 rpm / min for 8 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, with an active iron content of 3.2wt% and an active copper content of 2.6wt%.

[0073] Embodiment 13

[0074] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0075] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.1mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it three times with oxygen-free deionized water in an oxygen-free glove box; then add 200ml 1mol / L CuCl 2 The solution was heated and stirred for 1 h in a 30 °C water bath and under a magnetic stirring of 400 rpm / min, and the temperature was increased at a rate of 7.5 °C / h, and the mixture was heated and mixed for 2 h every time the temperature was increased by 10 °C, and the mixture was heated to 60 °C and mixed for 3 h to obtain a mixture I; the mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4and Cu 2+ The molar ratio of NaBH is 30:1 4 The suspension was quickly added, sealed quickly, reacted at room temperature for 1 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 0.5 mol / L FeCl 3 The solution was magnetically stirred at 400 rpm / min for 8 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, with an active iron content of 3.5wt% and an active copper content of 4.1wt%.

[0076] Embodiment 14

[0077] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0078] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.1mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it three times with oxygen-free deionized water in an oxygen-free glove box; then add 200ml 1mol / L CuCl 2 The solution was heated and stirred for 1 h in a 30 °C water bath and under a magnetic stirring of 400 rpm / min, and the temperature was increased at a rate of 7.5 °C / h, and the mixture was heated and mixed for 2 h every time the temperature was increased by 10 °C, and the mixture was heated to 60 °C and mixed for 3 h to obtain a mixture I; the mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 30:1 4 The suspension was quickly added, sealed quickly, reacted at room temperature for 1 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 0.5 mol / L FeCl 3 The solution was magnetically stirred at 400 rpm / min for 8 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, with an active iron content of 3.5wt% and an active copper content of 4.1wt%.

[0079] Embodiment 15

[0080] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0081] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.1mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it three times with oxygen-free deionized water in an oxygen-free glove box; then add 200ml 1mol / L CuCl 2 The solution was heated and stirred for 1 h in a 30 °C water bath and under a magnetic stirring of 400 rpm / min, and the temperature was increased at a rate of 7.5 °C / h, and the mixture was heated and mixed for 2 h every time the temperature was increased by 10 °C, and the mixture was heated to 60 °C and mixed for 3 h to obtain a mixture I; the mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 30:1 4 The suspension was quickly added, sealed quickly, reacted at room temperature for 1 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 0.5 mol / L FeCl 3 The solution was magnetically stirred at 400 rpm / min for 8 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, with an active iron content of 3.5wt% and an active copper content of 4.1wt%.

[0082] Example 16

[0083] A method for preparing a multi-active center catalytic oxidation material based on biotite, comprising the following steps:

[0084] Grind biotite to 200 mesh, weigh 5g biotite powder and add it to a 250ml conical flask, then add 200ml 0.1mol / L hydrochloric acid solution, mix under magnetic stirring at 400rpm / min for 30min, then remove the supernatant by high-speed centrifugation at 8000rpm, and wash it three times with oxygen-free deionized water in an oxygen-free glove box; then add 200ml 1mol / L CuCl 2The solution was heated and stirred for 1 h in a 30 °C water bath and under a magnetic stirring of 400 rpm / min, and the temperature was increased at a rate of 7.5 °C / h, and the mixture was heated and mixed for 2 h every time the temperature was increased by 10 °C, and the mixture was heated to 60 °C and mixed for 3 h to obtain a mixture I; the mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 30:1 4 The suspension was quickly added, sealed quickly, reacted at room temperature for 1 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 0.5 mol / L FeCl 3 The solution was magnetically stirred at 400 rpm / min for 8 hours at room temperature, and then washed three times with oxygen-free deionized water; a suspension of multi-active center oxidation catalytic material based on biotite was obtained, and the suspension was freeze-dried for 24 hours to obtain a multi-active center catalytic oxidation material based on biotite, with an active iron content of 3.5wt% and an active copper content of 4.1wt%.

[0085] Experimental Example 1 TEM test

[0086] The original biotite and the biotite-based multi-active center oxidation catalytic material prepared in Example 1 were observed by transmission electron microscopy. The results are as follows: Figure 1 As shown, Figure 1 (a) is a TEM image of the original biotite; (b) is a TEM image of the biotite-based multi-active center oxidation catalytic material involved in this application. Figure 1 It can be seen that the biotite mica layers after loading copper and iron atoms are clearer, which can prove that copper and iron have been loaded between the biotite mica layers.

[0087] Experimental Example 2: Methyl orange organic dye removal experiment

[0088] Materials used: The catalytic oxidation materials of Examples 1 to 12 were added at 2 g / L to a mixture containing organic dye methyl orange (molecular formula: C 14 H 14 N 3 SO 3 In the advanced oxidation system of sodium bicarbonate (Na, relative molecular mass 327.33) and persulfate, the system pH was adjusted to 3.0, the persulfate concentration was adjusted to 2 mmol / L, the organic dye concentration was 20 mg / L, and the advanced oxidation removal reaction was carried out by stirring with a stirrer. The removal rate of the organic dye was tested after 30 minutes, and each group was repeated three times.

[0089] Note: In Example 8, Group 1 added 0.092 g / L of nano copper powder to an advanced oxidation system containing an organic dye methyl orange (molecular formula: C14H14N3SO3Na, relative molecular mass 327.33) and persulfate; Group 2 added 0.076 g / L of iron salt to an advanced oxidation system containing an organic dye methyl orange (molecular formula: C14H14N3SO3Na, relative molecular mass 327.33) and persulfate; Group 3 added 0.076 g / L of iron salt and 0.092 g / L of nano copper powder to an advanced oxidation system containing an organic dye methyl orange (molecular formula: C14H14N3SO3Na, relative molecular mass 327.33) and persulfate.

[0090] Table 1

[0091]

[0092]

[0093] The results are shown in Table 1 and Figure 2-4 As shown, it can be seen from the data in Table 1 that in Example 5, no persulfate was added, and the organic dye was basically not degraded after 30 minutes, indicating that the material itself does not have degradation activity, and the material works by catalyzing PMS. The catalytic oxidation material based on biotite in Example 6 does not load copper, and some organic dyes are degraded after 30 minutes, indicating that the catalytic oxidation material based on biotite with iron alone has a certain catalytic degradation effect, but the degradation performance is greatly reduced. The catalytic oxidation material based on biotite in Example 7 does not load iron, and the organic dye is basically not degraded after 30 minutes, indicating that the catalytic oxidation material based on biotite with copper alone has no catalytic degradation effect, and needs to load bimetallic to form multiple active centers to catalyze degradation. The data of Example 8 proves that in the case of equal amounts of copper and equal amounts of iron, the catalytic degradation efficiency of the biotite-free mica is greater than that of the biotite-loaded catalytic degradation efficiency, but the catalytic degradation efficiency of the bimetallic multi-active site catalytic oxidation material with biotite load is greater than that of the bimetallic material without biotite load, and relative to the case of a single metal, the improvement of the catalytic degradation efficiency of the bimetallic multi-active site catalytic oxidation material with biotite load is greater than that of the bimetallic material without biotite load. Example 9 Since copper is not easily loaded to the biotite interlayer at a relatively low temperature, the metal content is relatively low, the active sites are relatively low, and the catalytic degradation efficiency is relatively low. Example 10 The metal content loaded to the biotite interlayer at a medium temperature is still relatively small, and not enough multi-active sites are formed, and the catalytic degradation efficiency is relatively low. While Example 11 loads copper to the biotite interlayer at a relatively high temperature, the content is sufficiently large, but the energy consumption is relatively high. The uniform heating rate of Example 12 does not allow copper atoms to have a good loading amount, does not form enough multi-active sites, and has a relatively low catalytic degradation efficiency.

[0094] In addition, by attaching Figures 2 to 4 It can be seen that Examples 1 to 4 have excellent catalytic performance based on biotite multi-active center oxidation catalytic materials. Figure 3 By comparing Examples 1 with 6, 7, and 8, it can be seen that the catalytic removal performance of the biotite multi-active center oxidation catalytic material is significantly better than that of the catalyst material without active components and with a single reaction center, and the catalytic activation efficiency of the bimetallic catalyst based on the biotite multi-active center oxidation catalytic material is much higher than that of the bimetallic catalyst without biotite. Figure 4 By comparing Examples 1 with 9, 10, 11, and 12, it can be seen that the catalytic removal performance of the biotite multi-active center oxidation catalytic material obtained by programmed temperature increase is significantly better than the catalytic removal performance of the biotite multi-active center oxidation catalytic material obtained by constant temperature and uniform temperature increase.

[0095] Experimental Example 3: Experiment on removal of different types of organic pollutants

[0096] The biotite multi-active center oxidation catalytic material prepared in Example 1 was subjected to different organic pollutant removal experiments (three repeated experiments were performed in each group). The amount of catalytic material added and the organic dye removal effect are shown in Table 2 and Figure 5 Note: The pH value of each organic dye system was adjusted to 3.0, the persulfate concentration was adjusted to 1 mmol / L, the organic dye concentration was 20 mg / L, and the mixture was stirred by a stirrer at a speed of 400 r / min.

[0097] From Table 2 and Figure 5 The data show that biotite-based multi-active center oxidation catalytic materials can efficiently activate and degrade a variety of organic pollutants, and have a good broad-spectrum degradation effect on a variety of organic pollutants.

[0098] Table 2

[0099]

[0100] Experimental Example 4: Stability Test

[0101] The material in Example 1, that is, the biotite, was ground to 200 mesh, 5 g of biotite powder was weighed and added to a 250 ml conical flask, and then 200 ml of 0.1 mol / L hydrochloric acid solution was added, and mixed under magnetic stirring at 400 rpm / min for 30 min, and then the supernatant was removed by high-speed centrifugation at 8000 rpm, and washed three times with oxygen-free deionized water in an oxygen-free glove box; then 200 ml of 0.1 mol / L CuCl 2The solution was heated at a rate of 10°C / h under a 20°C water bath and a magnetic stirring of 400 rpm / min, and the mixture was heated and mixed for 2 h every time the temperature was increased by 10°C, and the mixture was heated to 60°C and mixed for 2 h to obtain a mixture I; the mixture I was suspended in oxygen-free deionized water, and the pH of the suspension was adjusted to 1.5 with 1 mol / L hydrochloric acid. In a nitrogen atmosphere, NaBH 4 and Cu 2+ The molar ratio of NaBH is 30:1 4 The suspension was quickly added, sealed quickly, reacted at room temperature for 5 min, centrifuged at 8000 rpm to remove the supernatant, and washed three times with oxygen-free deionized water in an oxygen-free glove box to obtain zero-valent copper biotite material. The zero-valent copper biotite material was added with 200 ml 0.1 mol / L FeCl 3 The solution was stirred in a water bath at 20°C and at 400 rpm / min for 4 hours, and then washed three times with oxygen-free deionized water; a suspension of a biotite-based multi-active center oxidation catalytic material was obtained, and the suspension was freeze-dried for 24 hours to obtain a biotite-based multi-active center oxidation catalytic material with an iron content of 3.5wt% and a copper content of 4.1wt%.

[0102] The obtained multi-active center catalytic oxidation material based on biotite was added to a mixture containing organic dye methyl orange (molecular formula: C 14 H 14 N 3 SO 3 In the advanced oxidation system of Na, relative molecular mass 327.33) and persulfate, the system pH value was adjusted to 3.0, the persulfate concentration was adjusted to 2 mmol / L, the organic dye concentration was 20 mg / L, and the advanced oxidation removal reaction was carried out by stirring with a stirrer.

[0103] After 30 minutes of reaction, the biotite-based multi-active center oxidation catalytic material was washed three times with oxygen-free deionized water and then dispersed in a 0.5 mol / L FeCl 3 The material was placed in a 1 mol / L hydrochloric acid solution and stirred at 400 rpm / min for 0.5 h, then washed with oxygen-free deionized water for 3 times. After obtaining the material, the organic dye was degraded under the same degradation conditions for 5 cycles. Figure 6 As shown, after 5 cycles, the catalytic effect of the catalyst material obtained in Example 1 did not show obvious catalyst performance deactivation phenomenon, and the catalytic performance decline was controlled at about 10% after 5 cycles.

[0104] In summary, compared with traditional advanced catalytic oxidation materials, the biotite-based multi-active center oxidation catalytic material obtained by the present invention has a high content of copper and iron atoms, significantly improved reaction activity, high activity, excellent anti-aging performance, simple production steps, and the advantage of being reusable.

[0105] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing a multi-active center catalytic oxidation material based on biotite, characterized in that: The steps include: Step 1, dispersing biotite in a hydrochloric acid solution, mixing and stirring to obtain acid-pretreated biotite; Step 2, washing the acid pretreated biotite and mixing it with the copper salt solution, and then reacting it under gradient temperature control to obtain a mixture I; Step 3, dispersing the mixture I in deionized water, adjusting the pH value, mixing it with a reducing agent for reduction reaction, and washing with deionized water to obtain a mixture II; Step 4: Disperse the mixture II in an iron salt solution, stir, wash with deionized water, and freeze-dry to obtain a biotite-based multi-active center oxidation catalytic material.

2. The method for preparing a multi-active center catalytic oxidation material based on biotite according to claim 1, characterized in that: In step 1, the particle size of biotite is below 200 mesh, the concentration of hydrochloric acid is 0.1-1 mol / L, and the mixing and stirring time is 15-60 min.

3. The method for preparing a multi-active center catalytic oxidation material based on biotite according to claim 2, characterized in that: In step 2, the copper salt is at least one of CuCl2 and Cu(NO3)2, the concentration of the copper salt is 0.1-1 mol / L, and the addition ratio of the copper salt to biotite is 5g:(0.1-1 mol / L).

4. The method for preparing a multi-active center catalytic oxidation material based on biotite according to claim 3, characterized in that: In step 2, the gradient temperature control reaction is as follows: heating and stirring at 30°C for 1 h, then heating to 40°C at a rate of 10°C / h, heating and stirring for 2 h, then heating to 50°C at a rate of 10°C / h, heating and stirring for 3 h, then heating to 60°C at a rate of 10°C / h, heating and stirring for 4 h, then heating to 70°C at a rate of 10°C / h, heating and stirring for 5 h, then heating to 80°C at a rate of 10°C / h, and heating and stirring for 6 h.

5. The method for preparing a multi-active center catalytic oxidation material based on biotite according to claim 4, characterized in that: In step 3, the pH is adjusted to 1.2-1.

5.

6. The method for preparing a multi-active center catalytic oxidation material based on biotite according to claim 5, characterized in that: In step 3, the mixture I is dispersed in deionized water under anaerobic conditions at room temperature.

7. The method for preparing a multi-active center catalytic oxidation material based on biotite according to claim 6, characterized in that: In step 3, the reducing agent is NaBH4 or KBH4, the molar ratio of the reducing agent to the copper in the mixture I is 10 to 30:1, and the reduction reaction time is 1 to 5 minutes.

8. The method for preparing a multi-active center catalytic oxidation material based on biotite according to claim 7, characterized in that: In step 4, the iron salt is at least one of FeCl3 and Fe(NO3)3, the concentration of the iron salt is 0.1-1 mol / L, and the addition ratio of the iron salt to the mixture II is (0.1-1 mol / L): 5 g.

9. The method for preparing a multi-active center catalytic oxidation material based on biotite according to claim 8, characterized in that: In step 4, the freeze-drying temperature is less than 40° C. and the freeze-drying pressure is less than 10 Pa.

10. A multi-active-center catalytic oxidation material based on biotite, characterized in that: The material is prepared by any preparation method according to claims 1 to 9, wherein the content of active iron in the material is 3 to 4 wt%, and the content of active copper in the material is 3.5 to 4.6 wt%.